The Behavioral Consequence of Phenylketonuria in Mice Depends on the Genetic Background - Bruinenberg, Vibeke M.; van der Goot, Els; van Vliet, Danique; de Groot, Martijn J.; Mazzola, Priscila N.; Heiner-Fokkema, M. Rebecca; van Faassen, Martijn; van Spronsen, Francjan J.; van der Zee, Eddy A. (Frontiers in Behavioral Neuroscience, 2016)
To unravel the role of gene mutations in the healthy and the diseased state, countless studies have tried to link genotype with phenotype. However, over the years, it became clear that the strain of mice can influence these results. Nevertheless, identical gene mutations in different strains are often still considered equals. An example of this, is the research done in phenylketonuria (PKU), an inheritable metabolic disorder. In this field, a PKU mouse model (either on a BTBR or C57Bl/6 background) is often used to examine underlying mechanisms of the disease and/or new treatment strategies. Both strains have a point mutation in the gene coding for the enzyme phenylalanine hydroxylase which causes toxic concentrations of the amino acid phenylalanine in blood and brain, as found in PKU patients. Although the mutation is identical and therefore assumed to equally affect physiology and behavior in both strains, no studies directly compared the two genetic backgrounds to test this assumption. Therefore, this study compared the BTBR and C57Bl/6 wild-type and PKU mice on PKU-relevant amino acid- and neurotransmitter levels and at a behavioral level. The behavioral paradigms were selected from previous literature on the PKU mouse model and address four domains, namely 1) activity levels, 2) motor performance, 3) anxiety and/or depression-like behavior, and 4) learning and memory. The results of this study showed comparable biochemical changes in phenylalanine and neurotransmitter concentrations. In contrast, clear differences in behavioral outcome between the strains in all four above-mentioned domains were found, most notably in the learning and memory domain. The outcome in this domain seem to be primarily due to factors inherent to the genetic background of the mouse and much less by differences in PKU-specific biochemical parameters in blood and brain. The difference in behavioral outcome between PKU of both strains emphasizes that the consequence of the PAH mutation is influenced by other factors than Phe levels alone. Therefore, future research should consider these differences when choosing one of the genetic strains to investigate the pathophysiological mechanism underlying PKU-related behavior, especially when combined with new treatment strategies.